Nexus between firm fundamentals and financial leverage in Nepalese nonfinancial firms - Lamichhane, Pitambar (Management Dynamics, 2020)
This paper aims to analyze the nexus between firm fundamentals and financial leverage in Nepalese non-financial firms for the period 2000/01-2017/18 applying descriptive and causal comparative research design. Short-term, long-term and total financial leverage ratios are dependent variables and firm-fundamental variables are considered as explanatory variables. The result of this paper shows that Nepalese firms are highly levered. Regression results of this study reveals that profitability, earning variability, liquidity are major determinants of financial leverage. This study concludes that short-term financial leverage is positively affected by growth and earning variability whereas negatively affected by profitability, tangibility, and liquidity of firms. Similarly, long-term financial leverage is positively influenced by size, assets tangibility, and earning variability whereas negatively influenced by profitability and liquidity. Further, result of the paper reveals positive effect of assets tangibility and earning variability and negative effect of profitability and liquidity on total financial leverage. Finally, this paper concludes that firms’ non-debt tax shield and age of firms have no significant impact on financial leverage in Nepalese non-financial firms.